2001
DOI: 10.1063/1.1415446
|View full text |Cite
|
Sign up to set email alerts
|

Triplet-triplet annihilation in a poly(fluorene)-derivative

Abstract: We report on measurements of phosphorescence (Ph) and delayed fluorescence (DF) in poly(2,7-(9,9-bis(2-ethylhexyl)fluorene)) (PF2/6) present as dilute solid solution, as well as in bulk films. From combined experimental investigations of the time and intensity dependence of DF and Ph, as well as the temperature dependence of DF, we are able to show that DF in PF2/6, both in solution and film, is dominated by triplet-triplet annihilation (TTA). As a consequence of the intrachain diffusion and, hence, relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
137
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 13 publications
24
137
1
3
Order By: Relevance
“…The consequence of such a high density of triplet excited states in conjugated polymers has been studied previously, where it was found that the triplet decay is dominated by their mutual 2011) bimolecular annihilation (TTA), 22,23 resulting in the production of emissive singlet excitons. Figure 3(a) shows the time resolved electroluminescence during the turn off of the prototypical device.…”
Section: Resultsmentioning
confidence: 99%
“…The consequence of such a high density of triplet excited states in conjugated polymers has been studied previously, where it was found that the triplet decay is dominated by their mutual 2011) bimolecular annihilation (TTA), 22,23 resulting in the production of emissive singlet excitons. Figure 3(a) shows the time resolved electroluminescence during the turn off of the prototypical device.…”
Section: Resultsmentioning
confidence: 99%
“…For the triplet signal, either triplet transient absorption [90,101] or phosphorescence [85] could be used. However, both require large excitation densities to yield appropriate signal-to-noise ratios, which also causes migration activated TTA a major quenching channel [102,103]. The situation becomes (relatively) worse at higher temperature, because triplet mobility increases-at room temperature triplet excitons decay essentially only by TTA, without any phosphorescence emission [49,104].…”
Section: Experimental Observationsmentioning
confidence: 99%
“…(PBPMSi), σ = 94 meV [22]; and for poly(2,7-(9,9-bis(2-ethylhexyl)fluorene)) (PF2/6), σ = 40meV [12]. In contrast, DCM2:Alq 3 films possess considerably less disorder as reflected in their narrow DOS.…”
Section: Temperatures Below the Transition (Ie T < T Trans ) Multimentioning
confidence: 99%
“…Previous work has reported on the temperature dependence of triplet exciton transport in benzophenone glass [11], intrachain triplet diffusion and TTA in both solution and bulk films of a poly(fluorene) derivative [12], and triplet energy transfer in conjugated polymers [13][14][15]. While the dynamics of singlet excitons vs. temperature were explored in neat Alq 3 [16], to our knowledge the temperature dependence of emissive singlet and non-emissive triplet states has yet to be systematically studied in an efficient small molecule fluorescent guest-host system.…”
Section: Introductionmentioning
confidence: 99%